Effect of adjuvant trastuzumab among patients treated with anti-HER2-based neoadjuvant therapy - Gonzalez-Angulo, A M (Br J Cancer, 2015)
PURPOSE: To study the impact of adjuvant trastuzumab among patients achieving a pathologic complete response (pCR) after trastuzumab-based neoadjuvant systemic therapy (NST). PATIENTS AND METHODS: Patients with primary HER2-positive breast cancer treated with trastuzumab-based NST were categorised according to adjuvant trastuzumab administration and pCR status. Adjuvant trastuzumab became standard of care in 2006, this was the main reason patients in our cohort did not receive adjuvant trastuzumab. Kaplan–Meier was used to estimate survival. A test for interaction between adjuvant trastuzumab and pCR was completed. FINDINGS: Of 589 patients, 203 (34.5%) achieved a pCR. After surgery, 109 (18.5%) patients in the entire cohort did not receive adjuvant trastuzumab. Among patients achieving a pCR, 31.3% received adjuvant trastuzumab compared with 68.8% among those who did not achieve a pCR (P=0.0006). Among patients achieving pCR, adjuvant trastuzumab did not further improve overall survival (OS) or relapse-free survival (RFS) (P=0.35 and P=0.93, respectively). Any benefit of adjuvant trastuzumab in OS and RFS among patients without a pCR did not achieve statistical significance (P=0.3 and P=0.44, respectively). CONCLUSIONS: In this cohort, patients treated with trastuzumab-based NST who achieved a pCR have excellent outcome regardless of whether they received adjuvant trastuzumab.